2020
DOI: 10.13189/ujer.2020.080906
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking among Al-Balqa Applied University Students

Abstract: Critical thinking is a central part of our daily life. It has great importance in immunizing the individual against the vast amount of information, events, and situations that the individual deals with and faces. This study aimed at identifying differences in critical thinking according to different variables. The variables were specializations (scientific, literary), gender (male, female), the Grade Point Average (GPA) and the scores of Jordanian high school national exam (Tawjiji) to predict critical thinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, there are also other studies that revealed contradictory results on gender differences in CT skills. While some studies reported no significant difference by gender (Afsahi & Afghari, 2017;Özcan, 2017;Sur 2020), some studies concluded that males were ahead when compared to female students in CT skills (King, Wood, & Mines, 1990;Thayer-Bacon, 1993;Algharaibeh & ALmomani, 2020;Marni et al, 2020). Some researchers attributed females' success in CT to females' being more able to think critically and to arrange the way of their thinking than those of males.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are also other studies that revealed contradictory results on gender differences in CT skills. While some studies reported no significant difference by gender (Afsahi & Afghari, 2017;Özcan, 2017;Sur 2020), some studies concluded that males were ahead when compared to female students in CT skills (King, Wood, & Mines, 1990;Thayer-Bacon, 1993;Algharaibeh & ALmomani, 2020;Marni et al, 2020). Some researchers attributed females' success in CT to females' being more able to think critically and to arrange the way of their thinking than those of males.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…The cortical region of the male brain is primarily focused on spatial tasks, with only a small fraction dedicated to producing and processing words. Moreover, the ability to estimate the causes of the problems for males is easier as it is also related to the left side of the brain on which CT skills is higher compared to the right side of the brain used generally by females (Fuad et al, 2017;Algharaibeh & ALmomani, 2020;Marni et al, 2020). Besides these, considering the CT skills tests and their sub-dimensions, gender effect also varies from test to test in general and from one sub-dimension to another.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the same token, studies have concluded a noticeable deficiency in coherent organization of ideas, evidence, and arguments in assignments requiring extensive writing. Authors have blamed traditional instructor-centered teaching methods focusing on memorization rather than critical reasoning and problem solving [21,22].…”
Section: Assessment Of Critical Thinking Skills Among Arab College Studentsmentioning
confidence: 99%